ARTIFICIAL INTELLIGENCE AND INFORMATION SECURITY: INNOVATIVE SOLUTIONS IN CLOUD TECHNOLOGIES: https://doi.org/10.5281/zenodo.17240738 - Sharipov , Farid; Sharipova , Sadoqat (International scientific and practical conference, 2025)
This paper discusses the integration of artificial intelligence (AI) with cloud technologies and its role in ensuring information security. Special attention is given to modern solutions in financial technology and corporate services. Based on the experience of Basware, a leading Finnish company, the paper examines mechanisms for securing cloud environments and evaluates the effectiveness of intelligent systems in mitigating cyber threats.